Shift dynamics near non-elementary T-points with real eigenvalues. Issue 4 (3rd April 2018) - Knobloch, Jürgen; Lamb, Jeroen S. W.; Webster, Kevin N.
Abstract: We consider non-elementary T-points in reversible systems inR 2 n + 1 . We assume that the leading eigenvalues are real. We prove the existence of shift dynamics in the unfolding of this T-point. Furthermore, we study local bifurcations of symmetric periodic orbits occurring in the process of dissolution of the chaotic dynamics.